The Effect of The Jigsaw Cooperative Learning Model on Improving Cognitive Learning Outcomes of Grade 9 JHS Students in Static Electricity Material - Saldy, Mutia; Arif, Khairil (Universe, 2024)
This research was conducted to determine the effect of the jigsaw cooperative learning model on improving cognitive learning outcomes of 9th grade junior high school students on static electricity. This research was conducted at SMPN 31 Padang in an odd semester of the 2022/2023 school year. The type of research used is Quasi Experiment. The research design to be used is a non-equivalent control group design. The sampling technique used was purposive sampling. The sample used was class IX B as an experimental class with a jigsaw cooperative learning model and class IX A as a control class with a conventional learning model. The instrument used in this study was written in the form of multiple choice questions of 20 questions. While the test analysis was carried out using Microsoft Excel, the calculation of the hypothesis test was carried out by the t test after the prerequisite test was carried out, namely the normality test and homogeneity test. The results of the t-test calculation obtained tcount = 3.83 and ttable = 2.01, where tcount > ttable, thus H0 was rejected and H1 was accepted. This shows that there is an influence of the jigsaw cooperative learning model on the cognitive learning outcomes of class IX junior high school students on static electricity.